2010
DOI: 10.1007/s12245-009-0140-9
|View full text |Cite
|
Sign up to set email alerts
|

Medical student disaster medicine education: the development of an educational resource

Abstract: BackgroundDisaster medicine education is an enormous challenge, but indispensable for disaster preparedness.AimsWe aimed to develop and implement a disaster medicine curriculum for medical student education that can serve as a peer-reviewed, structured educational guide and resource. Additionally, the process of designing, approving and implementing such a curriculum is presented.MethodsThe six-step approach to curriculum development for medical education was used as a formal process instrument. Recognized exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 17 publications
0
50
0
1
Order By: Relevance
“…Pfenninger et al, at Johns Hopkins University, developed a similar course with 14 headlines using a six-step method. 11 The main similarity between the two studies lay in the headlines, which was due to the similarity in the nature of health management in crises. There were also some differences which may result from the differences that exist between crises and available resources in different communities.…”
Section: Communication In Crisesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pfenninger et al, at Johns Hopkins University, developed a similar course with 14 headlines using a six-step method. 11 The main similarity between the two studies lay in the headlines, which was due to the similarity in the nature of health management in crises. There were also some differences which may result from the differences that exist between crises and available resources in different communities.…”
Section: Communication In Crisesmentioning
confidence: 99%
“…10 Pfenninger et al, after a review of existing studies, indicated there were very few reported curricula and courses on health management in crises for medical students. 11 In order to enhance the knowledge and skills of medical students on how to understand the health-related issues in crises and to promote their ability to manage and deal with crises, such courses and curriculums for medical education are necessary. 10 This study was conducted at the Kurdistan University of Medical Sciences in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Medicinsko djelovanje najvažnije je u prva 24 sata od potresa: pružena pomoć mora biti brza i mora uključivati osnovne postupke za pružanje prve pomoći ozlijeđenima, napredne postupke saniranja ozljeda, kirurške postupke oživljavanja, anesteziju i analgeziju in situ te intenzivnu skrb. Medicinski djelatnici moraju biti osposobljeni za pružanje pomoći i u uvjetima nepostojanja bolničkih infrastruktura (eventualno u poljskim bolnicama) (38)(39)(40)(41)(42). Osobe koje su odgovorne za nadzor i koordinaciju medicinskog djelovanja moraju u svakom trenutku raspolagati podacima o broju i tipu ozljeda te o zdravstvenim posljedicama kako bi se organizirala djelotvorna pomoć.…”
Section: Zdravstveni Učinci Potresa I Zdravstvena Skrbunclassified
“…A German study presents the experience of building an academic curriculum for medical care in disaster cases, showing that knowledge and skills development in practical exercises can serve as basic training for medical practice in all types of emergency situations, a factor that can directly influence improvements in care delivery to victims (36) .…”
Section: Academic Education: the Fundamental Frameworkmentioning
confidence: 99%